Diagnostic Evolution of Synchronous Arteriovenous Malformation & Glioblastoma: A Case Report. (1st October 2022) - Davis, Jillian; Goldspring, Rob; Scott, Ian; Smith, Stuart; Chattopadhyay, Arpita
Abstract: AIMS: We present the clinical course, radiology and histopathology of a case with synchronous pathology and aim to highlight learning points and diagnostic pitfalls. METHOD: Case Notes, Radiology and Pathology were reviewed. RESULTS: A 25 year old female with learning difficulties presented acutely with collapse. Initial CT-imaging demonstrated a right peritrigonal parenchymal haematoma with intraventricular extension. CT-Angiography revealed small vessels around the haematoma but no definite underlying vascular abnormality. Whilst the standard MRI sequences appeared to confirm the CT findings, the patient was unable to tolerate the planned MR angiogram or post-contrast sequences. Three months later, Digital Subtraction Angiography (DSA) revealed an "unusual" arteriovenous malformation (AVM) at the site of the previous haematoma. Over the following two months, the patient represented twice with acute headaches. CT imaging each time demonstrated further re-bleeds, with increasing oedema. Consequently, another DSA was performed for attempted embolisation but striking differences in the appearance of the AVM were now evident. Stereotactic radiosurgery was scheduled, but a planning CT-scan six weeks later revealed, for the first time, appearances suggestive of an underlying high-grade neoplasm. A biopsy was performed which showed a Glioblastoma (CNS WHO, 2021; Grade 4) alongside an arteriovenous malformation with well-developed arterial and venous structures. Despite optimal ICU management post-operatively, the patient deteriorated and sustained irreversible brain damage from which she did not recover. CONCLUSION: Synchronous Glioblastoma and AVM is rare and can cause diagnostic and surgical challenges. These difficulties and the proposed angiogenic effects of tumour factors, as underlying aetiological agents of these synchronous lesions, is discussed.